Assessment of fractional excretion of urea for early diagnosis of cardiac surgery associated acute kidney injury. (26th November 2015) - Varela, Carlos Federico; Greloni, Gustavo; Schreck, Carlos; Bratti, Griselda; Medina, Angel; Marenchino, Ricardo; Pizarro, Rodolfo; Belziti, Cesar; Rosa-Diez, Guillermo
Abstract: Background : Acute kidney injury (AKI) is a common complication after cardiac surgery (CS). Recently, neutrophil gelatinase-associated lipocalin (NGAL) was shown to predict AKI development earlier than serum creatinine, but it is not widely used in clinical practice. Fractional excretion of urea (FeU) has been referred to as a useful tool to discriminate between prerenal and established AKI. The aim of our study is to evaluate the sensitivity and specificity of FeU, in the early diagnosis of AKI in patients undergoing CS. Methods : We performed a prospective study on adults undergoing CS. AKI was defined by AKIN criteria. Individuals suffering from CKD, were excluded. Sensitivity and specificity of FeU, fractional excretion of sodium (FeNa) and urine NGAL, measured at 1, 6 and 24 h following CS, were assessed. Results : We included 66 patients (26% female) aging 68 ± 11 years. AKI prevalence was 24% and mortality was 3.28%. Patients with AKI had a significantly lower FeU compared to those without AKI (23.89 ± 0.67% vs. 34.22 ± 0.58%; p < 0.05) 6 h after CS, but not at the 1- and 24-h time points. NGAL was also statistically significant between both groups. FeU showed a 75% sensitivity and 79.5% specificity; the AUC was 0.786. ROC analysis of FeU and NGAL yielded similar values ( p = NS). Conclusion : FeU is useful as an early biomarker to predict AKI after CS and it is comparable to the new biomarker NGAL.